Pain at the Cochlear Implant Site Requiring Device Removal in Pediatric Patients. (4th January 2022) - Shearer, A. Eliot; Wang, Alicia; Lawton, Maranda; Lachenauer, Catherine; Brodsky, Jacob R.; Poe, Dennis; Kenna, Margaret; Licameli, Greg
Abstract : Objectives: Idiopathic pain at the cochlear implant (CI) site outside of the immediate postoperative period is an uncommon occurrence but may necessitate device explantation. Our objective was to describe the clinical course for pediatric patients with CI site pain who ultimately required device explantation. Study Design: Retrospective chart review. Methods: We performed a retrospective database review of CIs performed at a tertiary referral center for pediatric cochlear implantation. We specifically evaluated pediatric patients who presented with pain at or near the CI device site and ultimately required explantation. Results: Fifteen patients (16 CIs) had pain at or near the CI site requiring device explantation. Cultures taken during site exploration or device explantation identified bacteria in 86% and 81% of procedures, respectively. Propionibacterium acnes and Staphylococcus non‐ aureus were the most commonly identified organisms. Conclusions: The majority of patients with idiopathic pain in this cohort ultimately requiring CI explantation had chronic bacterial colonization. Level of Evidence: 4 (Case series) Laryngoscope, 132:2044–2049, 2022